The Risk–Need–Responsivity Model and Justice-Involved Persons with Serious Mental Illness - Bonta, James (Canadian journal of criminology and criminal justice, 2025)
The assessment and rehabilitation of justice-involved persons with serious mental illness (SMI) present unique challenges to the criminal justice system. For persons without mental health challenges, the risk-need-responsivity (RNR) model has had an enormous impact on what to assess and how best to deliver treatment to those in need. This paper poses the general question, Is RNR relevant to justice-involved persons with SMI? We argue that the critical risk/need factors, called the Central Eight, are as important to those with SMI as they are to those with no SMI. Unfortunately, assessment protocols that incorporate the Central Eight are quite rare in the literature. When we turn to lessons from the RNR model for the rehabilitation of justice-involved persons with SMI the research is even more scant. On a positive note, we provide an illustration of an RNR-based model of community supervision that demonstrates reductions in general and violent recidivism, STICS. The STICS model serves as an example of how effective treatment can be applied with persons with SMI.